Analysing cycling as a social practice: An empirical grounding for behaviour change. (February 2015) - Spotswood, Fiona; Chatterton, Tim; Tapp, Alan; Williams, David
Graphical abstract: Highlights: Traditional approaches encouraging utility cycling have failed to make sufficient impact. Social Practice Theory is used to analyse data about the 'image of cycling' held by cyclists and non-cyclists. Data are discussed in a disaggregated form and links between the elements identified and explored. The theory's potential for underpinning behaviour change interventions in the utility cycling field is explored. Abstract: Despite significant national and local efforts over the last decade to stimulate uptake of cycling in the UK, levels of cycling (particularly utility cycling) remain at around 2% of journeys. Understanding of cycling behaviour and subsequent development of interventions has typically been undertaken using an individualist approach, often relying on psychologically based models of behaviour. This paper argues that Social Practice Theory (SPT) may be a valuable addition to practitioner's toolboxes by providing an alternative means of understanding the complex dynamics between the elements that constitute the practice of utility cycling, allowing it to be considered as a social issue, rather than focusing solely on individual behaviour. This is demonstrated within the paper by the use of SPT to reanalyse quantitative and qualitative datasets that explore views and experiences of both cyclists and non-cyclists. Therein, the practice of utility cycling is described according to its three elements; materials, meaning and competences and the potential benefits of this approach are discussed; particularly its ideological shift away from 'victim blaming' and its natural support of interdisciplinary intervention design.